Knowledge, attitude and screening behaviour of Benue State University male students towards prostrate cancer awareness (2014)
The study investigated the influence of knowledge, attitude and screening behaviour of Benue State University Male Students towards prostate cancer awareness. Five research questions and research hypotheses guided the study. The study was a cross-sectional design utilizing a pretested 34-item Prostate Cancer Questionnaire (PCQ) (Cronbach’s alpha of 0.62) to collect information about knowledge, attitude and screening behavior regarding prostate cancer among Benue State University Male students Makurdi, Nigeria. Two hundred and forty-five participants were sampled for the study by systematic random selection of male students in Benue state university. Data analysis was done using mean and standard deviations while multiple regression analysis was used to test the hypotheses at 0.05 and 0.01 levels of significance respectively using SPSS 16.0 software. Result showed that the interaction of knowledge, attitude and screening behaviour significantly influenced prostate cancer awareness, knowledge (β=0.76; P<0.01), screening behaviour (β=0.108; P<0.05) and attitude (β=-0.018; P>0.05). Though attitude was not significant, their joint interaction significantly influenced awareness of prostate cancer. Demographic variables were not found to significantly influence prostate cancer awareness. The study provides conclusion for male students to be encouraged to follow health seeking behaviours and recommend that the government should design an intervention program through innovative health education strategies and include cancer education in school curriculum.